دور تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمة المالية البريدية - بن سماعين, حياة; بوغديري, حكيمة (Recherches économiques et managériales, 2018)
هدفت هذه الدراسة إلى التعرف على دور تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمة المالية البريدية المقدمة إلى متلقي الخدمة، من خلال إجراء دراسة تحليلية لوحدة البريد الولائية بسكر ة، حيث توصلنا إلى أن تكنولوجيا المعلومات والاتصال تساهم بدرجة ضعيفة في تحسين جودة الخدمة المالية البريدية لا لعدم توفر الوسائل اللازمة لذلك لكن يعود عزوف زبائن وحدة البريد الولائية بسكرة عن استخدام البطاقات المغناطيسية راجع لعدم توفر أبعاد جودة الخدمة : الجوانب الملموسة، درجة الاعتمادية، درجة الاستجابة، درجة الأمان، درجة التعاطف . الكلمات المفتاحية : الخدمة، الجودة، جودة الخدمة، تكنولوجيا المعلومات والاتصال، الإدارة الإلكترونية، الخدمة الإلكترونية، الخدمة المالية البريدية الإلكترونية . Abstract : The aim of this study was to identify the role of information and communication technology in improving the quality of the postal financial service provided to the recipients through an analytical study of the postal unit of Biskra. we found that information and communication technology has a small contribution to the improvement of the quality of the postal service, not because of the lack of means. However, the reluctance of the customers of the Post Office in Biskra is due to the use of magnetic cards and the absence of quality service dimensions: the concrete aspects, the degree of reliability, degree of response, degree of safety, degree of empathy Key words : service , quality , quality of service , information and communication technology , e-governance, e-service , e- financial and postal services.